t(1;3)(p36;p21) as the Sole Clonal Abnormality in Refractory Acute Myeloid Leukemia - Bai, MD, Bing; Lu, MD, Gary; Hu, MD, PhD, Shimin; Yin, MD, PhD, C. Cameron (North American Journal of Medicine and Science, 2012)
Acute myeloid leukemia (AML) is a heterogeneous group of diseases with a multitude of molecular genetic aberrations and variable clinical outcome. Clonal chromosomal abnormalities have been identified in over 50% of AML cases, and have been regarded as one of the most important prognostic markers. We present a case of a 56-year-old Hispanic man with AML with minimal differentiation. Morphologically, the bone marrow was hypercellular with trilineage hypoplasia and 80% blasts. Flow cytometry analysis showed that the blasts were of myeloid immunophenotype. Conventional cytogenetic analysis showed t(1;3)(p36;p21) as the sole cytogenetic abnormality in 5 of 20 metaphases analyzed. The patient received daunorubicin and cytarabine, and achieved first remission. He relapsed 4 months later, and was treated with fludarabine, cytarabine, idarubicin, and G-CSF, and consolidated with high-dose cytarabine. He then received matched related stem cell transplantation. However, the disease relapsed again, and the patient died 11 months after initial diagnosis. To our best knowledge, this is the first report of t(1;3)(p36;p21) as the sole cytogenetic abnormality.